2000
DOI: 10.1074/jbc.m003370200
|View full text |Cite
|
Sign up to set email alerts
|

Bid-induced Cytochrome c Release Is Mediated by a Pathway Independent of Mitochondrial Permeability Transition Pore and Bax

Abstract: Bid, a pro-apoptosis "BH3-only" member of the Bcl-2 family, can be cleaved by caspase-8 after Fas/TNF-R1 engagement. The p15 form of truncated Bid (tBid) translocates to mitochondria and induces cytochrome c release, leading to the activation of downstream caspases and apoptosis. In the current study, we investigated the mechanism by which tBid regulated cytochrome c release in terms of its relationship to mitochondrial permeability transition and Bax, another Bcl-2 family protein. We employed an in vitro reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
145
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(174 citation statements)
references
References 53 publications
23
145
0
5
Order By: Relevance
“…Furthermore, due to the unavailability of commercial antibodies, we could not distinguish between full length and truncated Bid. However, as previously mentioned, both forms possess apoptogenic properties (Kim, Zhao, Barber, Kuharsky, and Yin 2000;Konig, Rehm, Gudorf, Krajewski, Gross, Ward, and Prehn 2007). Therefore, an increased mitochondrial content of Bid, regardless of its cleavage, may still be considered as part of the pro-apoptotic environment taking place in aged skeletal muscle.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, due to the unavailability of commercial antibodies, we could not distinguish between full length and truncated Bid. However, as previously mentioned, both forms possess apoptogenic properties (Kim, Zhao, Barber, Kuharsky, and Yin 2000;Konig, Rehm, Gudorf, Krajewski, Gross, Ward, and Prehn 2007). Therefore, an increased mitochondrial content of Bid, regardless of its cleavage, may still be considered as part of the pro-apoptotic environment taking place in aged skeletal muscle.…”
Section: Discussionmentioning
confidence: 85%
“…While this finding may be interpreted as a compensatory action aimed at preventing myonuclei loss, we found a concomitant increase of total mitochondrial content of Bid. Recent experimental evidence indicates that full length Bid and tBid are sufficient to elicit mitochondrial cell death pathways (Kim et al 2000;Konig et al 2007). In an elegant experiment, Scorrano and coworkers (Scorrano et al 2002), demonstrated that tBid induced a dose-dependent release of cytochrome c from isolated mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…TRAIL treatment induced the loss of full-length Bid consistent with caspase-8-dependent Bid cleavage (13). Translocation of Bid to the mitochondria has been shown to engage the intrinsic apoptotic pathway after a death receptor stimulus such as TRAIL (12,14). Furthermore, the TRAILinduced cleavage of DFF45, a substrate of caspase-3, was completely blocked in SW480/Bcl-2 cells in contrast to SW480/neo cells (Fig.…”
Section: Bcl-2 Overexpression Protects Against Trail-inducedmentioning
confidence: 83%
“…1 Schematic diagram of the death receptor-mediated "extrinsic" and mitochondrial or "intrinsic" apoptotic pathways. Signals originating from membrane death receptors may cross-talk with the mitochondria by caspase-8-mediated cleavage of the proapoptotic Bcl-2 family member, Bid (12)(13)(14). Bid is then translocated to mitochondria where it can trigger cytochrome c release.…”
Section: Methodsmentioning
confidence: 99%
“…Also, in ANT-deficient hepatocytes no altered apoptosis responses to the ligands of the Fas-and the TNF-receptor were observed. However, it is contentious [109,110] whether the PT-pore in mitochondria is activated by these cell death signals that act at the plasma membrane and hence whether an altered apoptosis (and necrosis) response could have been expected. Furthermore, since this study was published another isoform of ANT (ANT4) has been discovered in the mouse genome [111].…”
Section: Ant Knock-out Studiesmentioning
confidence: 99%